- #1

vysero

- 134

- 0

Vf=Vi+at

I want to solve for t so:

(Vf-Vi)/a = t

right so now my problem starts how can this happen:

t = -Vf/a ?

The solution above comes from this site http://www.monmsci.net/~fasano/phys1/Chapter_2_10.pdf

scroll down to problem 2.31 and you will find what I am looking at, in this situation Vi = 0 so they disregarded it and somehow during that process (at least i believe it was during that process) they came up with:

t = -Vf/a

Please explain to me how that works, where the heck did the - sign come from??